2022
DOI: 10.3389/fnut.2022.853058
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and Depression

Abstract: Depression has become one of the most common mental diseases in the world, but the understanding of its pathogenesis, diagnosis and treatments remains insufficient. Carnitine is a natural substance that exists in organisms, which can be synthesized in vivo or supplemented by intake. Relationships of carnitine with depression, bipolar disorder and other mental diseases have been reported in different studies. Several studies show that the level of acylcarnitines (ACs) changes significantly in patients with depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 104 publications
0
14
1
Order By: Relevance
“…Higher levels of acyl carnitine metabolites were observed in men with abnormal depression and phobia scores, but the opposite direction of effect estimate was observed for anxiety, suggesting that depleted levels of these metabolites may be associated with worse scores in anxiety. Carnitine is often supplemented to alleviate depression [ 47 ], but our results were not consistent with the beneficial effects of carnitine supplementation observed in previous studies. This could be due to the fact that our study relied on self-reported scores while previous findings involved comparisons of metabolites with discrete clinical diagnoses [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Higher levels of acyl carnitine metabolites were observed in men with abnormal depression and phobia scores, but the opposite direction of effect estimate was observed for anxiety, suggesting that depleted levels of these metabolites may be associated with worse scores in anxiety. Carnitine is often supplemented to alleviate depression [ 47 ], but our results were not consistent with the beneficial effects of carnitine supplementation observed in previous studies. This could be due to the fact that our study relied on self-reported scores while previous findings involved comparisons of metabolites with discrete clinical diagnoses [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the future, longitudinal studies will be necessary to capture trajectories of changes over time in AC levels and depressive symptoms in order to properly disentangle trait vs state effects and provide empirical grounding for causal interpretation, triangulating evidence with experimental medicine approaches. To date, only few small studies with heterogeneous methodology tested carnitine/acetylcartinitine supplementation in depressed patients, producing inconsistent results [41] . In parallel, in-depth mechanistic studies could identify the precise biological mechanisms underlying the association between ACs and depression.…”
Section: Discussionmentioning
confidence: 99%
“…A possible exogenous cause is the higher intake of carnitine-rich foods in men, including meat, dairy products, and certain types of fish [45,46]. In non-vegetarians, 75% of the carnitine source is obtained from food, while the endogenous 25% relies on self-production and renal reabsorption related to the maintenance of homeostasis [47]. There is also a possibility that it is related to variability in absorption.…”
Section: Discussionmentioning
confidence: 99%